Experts vs. novices tagging behavior: an exploratory analysis - Špiranec, Sonja; Ivanjko, Tomislav (2013)
The universe of knowledge is not exclusively put in order by professionals any more. Traditional expert-oriented approaches are supplemented by organically-evolving user-generated approaches known as folksonomies. Their potentials (and disadvantages) as a new form of knowledge organization needs to be critically evaluated and scrutinized. This paper will review the notion of organization of information in contemporary information environments and contribute to findings and research data on tagging and folksonomies. The authors present results of a study in tagging behavior of an expert and novice group of users. By conducting the research on the student population two questions are being explored: a) what are specific differences in tagging behavior between experts and novices, and b) is the expertise acquired by students through course credits enough to create a significant difference in regard to the novice group with no formal education in the area. Differences of the two user groups in tag assignment are being analyzed with regard to tag number and distribution, both by using descriptive statistic and by introducing the tag efficiency measure. The results have shown that different efficiency levels in tag assignment between the two groups indicating that users with more knowledge and expertise could create folksonomies of higher quality.
Projekt MZOS
ENG